2022
DOI: 10.3390/ani12091076
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Egg Quality and Yolk Lipid Oxidation in Laying Hens Fed Diets including Grape Pomace or Grape Extract

Abstract: An experiment was conducted to assess in laying hens the effect of including grape pomace (GP, at 30 or 60 g/kg) or grape extract (GE, at 0.5 or 1.0 g/kg) on egg production, feed conversion ratio, protein and polyphenol digestibility, egg weight, egg quality, yolk fatty acid profile and oxidative stability of yolk lipids. No differences were detected among diets for egg production (83.8%, on average) or egg mass (56.8 g/d, on average). However, the average egg weight was lower (p = 0.004) for dietary treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Little information exists about the impact of supplementing grape by-products on yolk color and Haugh units in layers. Our findings are in harmony with Romero et al [11], who observed that supplementing laying hens' diets with GP increased egg yolk color score and Haugh units. Similarly, Fróes et al [46] reported a positive quadratic correlation between yolk coloration and dietary GP concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Little information exists about the impact of supplementing grape by-products on yolk color and Haugh units in layers. Our findings are in harmony with Romero et al [11], who observed that supplementing laying hens' diets with GP increased egg yolk color score and Haugh units. Similarly, Fróes et al [46] reported a positive quadratic correlation between yolk coloration and dietary GP concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidant effects of GP, grape seed, and their extracts have been the topic of research, with the emphasis that these products have a high possibility of improving the shelf-life of animal products by mitigating lipid peroxidation [11,13,14,38,45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…These effects are often attributed to the high concentrations of grape polyphenols, specifically condensed tannins, present in these byproducts (Romero et al. 2022 ). These condensed tannins have been found to bind to proteins, leading to a reduction in protein digestibility.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ; Romero et al. 2022 ). These compounds have been shown to possess stronger antioxidant properties compared to that of vitamins (Bagchi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation